Are University Co-operative Education Students Safe? Perceptions of Risk to Students on Work Terms - Newhook, Rebecca (Canadian Journal of Higher Education, 2016)
As students venture off campus for university-sponsored activities, are they at risk, given that universities are better able to control risk factors on campus than they can for their off-campus activities? Co-operative education is a formalized and longstanding academic program that often sees students spend upwards of a third of their time off campus during the completion of a degree; thus, a discussion of the risks in co-operative education could provide a basis for assessing levels of risk for other off-campus activities. This qualitative, descriptive case study examines co-operative education co-ordinators’ perceptions of the risks to students in co-operative education programs in Canadian universities. Fourteen co-ordinators from across Canada participated in one-on-one interviews. Co-ordinators acknowledged that of the partners in co-operative education, the student is the most at risk. However, they viewed co-operative education as a safe endeavour for students, and there was agreement that the actual risk to students is minimal. The risk factors identified by co-ordinators included personal safety, harassment, youth or limited life experience, and mental health.